The perceptibility of the frequency drop caused by the Doppler effect for simulated sound source motion in the median plane - JORASZ, U.; DOOLEY, G.J. (Archives of Acoustics, 1996)
Simulations of constant velocity (10 m/s and 20 m/s), pure-tone (1 kHz and 2 kHz) sound source moving in the median plane relative to a stationary observer were set up. The simulations were either simulations of approaching sources which stopped at the point of closest passing or of retreating source which began at the point of closest passing. The durations required for the detection of the Doppler-induced frequency drop were determined in a two-alternative, forced-choice task. One interval contained the Doppler-induced frequency drop and in the other the frequency was kept constant. Two types of signals were used: One simulated frequency and level changes which would occur for a moving source. The other simulated only the frequency changes, with the level steady at 65 dB SPL. Threshold durations were determined for simulations of both approaching and retreating source. The pattern of results was similar for all three subjects. In general, the faster the source the smaller the duration needed to detect the frequency drop. Source frequency had little effect on the duration thresholds indicating that a constant percentage frequency change may be required.